Unformatted text preview: the third one must be. If we set x = 0 = y, then substitution into the equation yields z = 5 , so we can use as our basepoint P (0 , , 5) (which is the intersection of P with the z-axis). We could ²nd the intersections of P with the other two axes in a similar way. Alternatively, we could notice that x = 1 y = − 1 means that 2 x − 3 y = 5 , so z = 0 and we could equally well use as our basepoint P ′ (1 , − 1 , 0) ....
View Full Document
This note was uploaded on 10/20/2011 for the course MAC 2311 taught by Professor All during the Fall '08 term at University of Florida.
- Fall '08